Root allocation and foraging precision in heterogeneous soils - Tara K. Rajaniemi (Basic and Applied Ecology, 2022)
Root growth patterns respond to small-scale resource heterogeneity and the presence of roots of neighboring plants, but how a plant integrates its responses to these cues is not well understood. In the presence of neighbors, plants may shift allocation to roots as a consequence of plant size and root:shoot allometry, as a response to resource depletion by neighbors, or through a direct response to neighbor presence. The same response pathways also have the potential to alter proliferation in resource-rich patches in soil.Four species of grassland plants were grown in the greenhouse as single plants, monocultures, and mixtures. Root length allocation as a function of shoot mass was examined for background soil and fertilized patches. Plants grown with same-species neighbors followed the same allometric trajectory as single plants for root length in background soil, so any change in root allocation was due only to reduced plant size. Root proliferation in patches declined with neighbors, consistent with a response to resource depletion. Mixtures overproduced roots in both background soil and in patches, relative to plants of the same size in monocultures.